2000
DOI: 10.1021/je000008o
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Acidic Solutes between Water and Supercritical Carbon Dioxide. Effect of pH and Ionic Strength

Abstract: Partitioning of pentachlorophenol (PCP) between water and CO 2 was investigated to determine the effects of pH and ionic strength on the value of the distribution coefficient, K. Decreasing the pH or increasing the ionic strength increased the value of K. The distribution coefficient was larger than that predicted by considering the extent of hydrolysis of the solute in the aqueous phase. However, impedance measurements suggest that negligible concentrations of ions exist in the CO 2 phase. Together, these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…These compounds include 2,4-dichlorophenol [14], phenol [55][56][57], p-chlorophenol, m-cresol, and benzene [57], toluene [58], a PAH mixture [15], naphthalene, phenanthrene, hexachlorobenzene, and pentachlorophenol [10,13,16]. Partitioning isotherms are also reported for the solutes pentachlorophenol, 2,3,4,5-tetrachlorophenol and 2,4-dichloro-phenoxyacetic acid between water and SCCD at about 40 • C and 100-270 bar [59].…”
Section: Partition Equilibriamentioning
confidence: 94%
“…These compounds include 2,4-dichlorophenol [14], phenol [55][56][57], p-chlorophenol, m-cresol, and benzene [57], toluene [58], a PAH mixture [15], naphthalene, phenanthrene, hexachlorobenzene, and pentachlorophenol [10,13,16]. Partitioning isotherms are also reported for the solutes pentachlorophenol, 2,3,4,5-tetrachlorophenol and 2,4-dichloro-phenoxyacetic acid between water and SCCD at about 40 • C and 100-270 bar [59].…”
Section: Partition Equilibriamentioning
confidence: 94%
“…Similar to thermodynamic modeling for trace inorganic elements, we cannot currently predict the eff ect of electrolytes in the aqueous phase on the partitioning behavior of organic compounds in sc-CO 2 . Curren and Burk, 46 measuring the partitioning of pentachlorophenol between water and sc-CO 2 as a function of NaCl concentration, found an increase in pentachlorophenol activity when salinity increased consistent with the 'salting out' eff ect. Xie et al 47 showed that the salting out eff ect was greater for organic compounds with a high molar volume.…”
Section: Solubility Of Organic Compounds In Supercritical Comentioning
confidence: 94%
“…The decrease in brine pH facilitates organic acid protonation and partition to sc‐CO 2 . This is consistent with lower water solubility and in agreement with Curren and Burk 2000's estimated K‐factors …”
Section: Solubility Of Organic Compounds In Supercritical Co2mentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental K-factor data were taken from the original sources. 13−26 However, some of the solutes, notably pentachlorophenol, 19 2,3,4,5-tetrachlorophenol, 21 3-methyl-4-chlorophenol, 22 and 2-methyl-4,6-dinitrophenol 22 and propiophenone 23 were omitted because of the lack of vapor pressure data at the required temperatures (see below). Therefore, the most extensive set of experimental Kfactor data comprised 455 data points for 44 solutes of diverse structures and falling within the temperature range of 297−363 K and the pressure range of 2.5−31.5 MPa.…”
Section: ■ Introductionmentioning
confidence: 99%